2007
DOI: 10.1016/j.freeradbiomed.2007.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-associated NAD(P)H oxidase contributes to the thrombogenic phenotype induced by hypercholesterolemia

Abstract: Elevated cholesterol levels promote pro-inflammatory and prothrombogenic responses in venules and impaired endothelium-dependent arteriolar dilation. Although NAD(P)H oxidase-derived superoxide has been implicated in the altered vascular responses to hypercholesterolemia, it remains unclear whether this oxidative pathway mediates the associated arteriolar dysfunction and platelet adhesion in venules. Platelet and leukocyte adhesion in cremasteric postcapillary venules, and arteriolar dilation responses to acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 42 publications
4
40
0
Order By: Relevance
“…27 It has been suggested that the increased NO release in arterial rings exposed to IFN-␥ leads to desensitization of the smooth muscle cell to NO, thereby impairing endothelium-dependent vasodilation. 11 Alternatively, the ability of IFN-␥ to induce NAD(P)H oxidase, 14,15 a superoxide-generating enzyme that contributes to hypercholesterolemia-induced arteriolar dysfunction, 24 may explain the actions of the cytokine in our model. IFN-␥ may also be acting indirectly by inducing the expression of or acting in concert with other cytokines such as TNF-␣ to alter NO bioavailability or oxygen free radical generation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…27 It has been suggested that the increased NO release in arterial rings exposed to IFN-␥ leads to desensitization of the smooth muscle cell to NO, thereby impairing endothelium-dependent vasodilation. 11 Alternatively, the ability of IFN-␥ to induce NAD(P)H oxidase, 14,15 a superoxide-generating enzyme that contributes to hypercholesterolemia-induced arteriolar dysfunction, 24 may explain the actions of the cytokine in our model. IFN-␥ may also be acting indirectly by inducing the expression of or acting in concert with other cytokines such as TNF-␣ to alter NO bioavailability or oxygen free radical generation.…”
Section: Discussionmentioning
confidence: 98%
“…Reduced nitric oxide (NO) bioavailability and enhanced NAD(P)H oxidasederived superoxide generation have both been implicated in the impaired dilation. 10,23,24 Because IFN-␥ is a potent stimulator of NAD(P)H oxidase, 14,15 it is plausible that T-lymphocytes, acting through release of this cytokine, may contribute to this arteriolar dysfunction. Using lymphocytedeficient mice, we have obtained evidence that strongly implicates T-cells in the impaired endothelium-dependent vasodilation in arterioles of hypercholesterolemic mice.…”
Section: Discussionmentioning
confidence: 99%
“…57 In patients with hypercholesterolemia, platelet-associated NAD(P)H oxidase produces a thrombogenic phenotype and mediates the arteriolar dysfunction. 20 Platelet superoxide production in patients with hypertension alone and in patients with coexistent diabetes mellitus has been examined. It was shown that eNOS can reside in the uncoupled state in patients with hypertension and, to a greater extent, in patients with coexisting hypertension and diabetes, and that this contributes significantly to increased superoxide production in these disease states.…”
Section: Platelets Oxidative Stress and Diseasementioning
confidence: 99%
“…These results implicate CD40/CD40L interactions between circulating cells and the vascular wall in both the arteriolar and venular dysfunction elicited by hypercholesterolemia and identify T-cell-associated CD40L as a key mediator of these responses. T lymphocytes; platelets; oxidative stress; arteriolar vasodilation; leukocyte adhesion HYPERCHOLESTEROLEMIA IS A well-characterized cardiovascular risk factor that is known to initiate inflammatory and thrombogenic responses in the microvasculature (34,35,41,42). These vascular reactions reflect a systemic low-level inflammatory phenotype that appears to predispose the microvasculature to larger injury responses following an exposure to other inflammatory stimuli, such as ischemia-reperfusion (14, 17).…”
mentioning
confidence: 99%
“…T lymphocytes; platelets; oxidative stress; arteriolar vasodilation; leukocyte adhesion HYPERCHOLESTEROLEMIA IS A well-characterized cardiovascular risk factor that is known to initiate inflammatory and thrombogenic responses in the microvasculature (34,35,41,42). These vascular reactions reflect a systemic low-level inflammatory phenotype that appears to predispose the microvasculature to larger injury responses following an exposure to other inflammatory stimuli, such as ischemia-reperfusion (14,17).…”
mentioning
confidence: 99%